Auction-Based Resource Allocation for Cooperative Video Transmission Protocols over Wireless Networks. (7th June 2009) - Han, Zhu; Su, Guan-Ming; Wang, Haohong; Ci, Song; Su, Weifeng
Abstract : Cooperative transmission has been proposed as a novel transmission strategy that takes advantage of broadcast nature of wireless networks, forms virtual MIMO system, and provides diversity gains. In this paper, wireless video transmission protocols are proposed, in which the spectrum resources are first allocated for the source side to broadcast video packets to the relay and destination, and then for the relay side to transmit side information generated from the received packets. The proposed protocols are optimized to minimize the end-to-end expected distortion via choosing bandwidth/power allocation, configuration of side information, subject to bandwidth and power constraints. For multiuser cases, most of current resource allocation approaches cannot be naturally extended and applied to the networks with relay nodes for video transmission. This paper extends the share auction approach into the cooperative video communication scenarios and provides a near-optimal solution for resource allocation. Experimental results have demonstrated that the proposed approach has significant advantage of up to 4 dB gain in single user case and 1.3 dB gain in multiuser case over the reference systems in terms of peak-to-signal-noise ratio. In addition, it reduces the formidable computational complexity of the optimal solution to linear complexity with performance degradation of less than 0.3 dB.